1993
DOI: 10.1111/j.1600-0773.1993.tb01551.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Hepatic Microsomal Drug Metabolism by Atracurium Administration in the Rat

Abstract: The muscle relaxant atracurium is known to undergo extrahepatic degradation via Hofmann elimination and ester hydrolysis. The purpose of the present study was to evaluate the effects of atracurium on hepatic P450-dependent enzyme activities. Thirty-two male Sprague-Dawley rats were anaesthetized, mechanically ventilated, and randomly allocated to one of four study groups: group 1 received saline, group 2 atracurium, group 3 vecuronium, and group 4 pancuronium intravenously for a period of 3 hr. Equipotent dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Ono et al (1996) used a recombinant vaccinia virus system and showed that the metabolism of diazepam in HepG2 cells is mediated by CYP3A4 as well as CYP2C19, which has been reported as a polymorphic enzyme, in human liver. Vecuronium is subject to the catalytic activity of CYP1A1 and CYP2B in rat microsomes (Bohrer et al 1993) while cimetidine and clonidine are not known to undergo CYP‐catalyzed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Ono et al (1996) used a recombinant vaccinia virus system and showed that the metabolism of diazepam in HepG2 cells is mediated by CYP3A4 as well as CYP2C19, which has been reported as a polymorphic enzyme, in human liver. Vecuronium is subject to the catalytic activity of CYP1A1 and CYP2B in rat microsomes (Bohrer et al 1993) while cimetidine and clonidine are not known to undergo CYP‐catalyzed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Ono et al (16) using a recombinant vaccinia virus system, showed that the metabolism of diazepam in HepG2 cells is mediated by CYP3A4 as well as CYP2C19, which has been reported as a polymorphic enzyme, in human liver. Vecuronium and pancuronium are subject to the catalytic activity of CYP1A1 and CYP2B in rat microsomes (17). However, pentobarbital, cimetidine, suxamethonium and clonidine are not known to undergo P450-catalysed metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Vecuronium and pancuronium are subject to the catalytic activity of CYP1A1 and CYP2B in rat microsomes. 8 On the other hand, pentobarbital, cimetidine, suxamethonium and clonidine are not known to undergo P450-catalyzed metabolism.…”
Section: Discussionmentioning
confidence: 99%